Dinamika Pesan Iklan - Eko Harry Susanto (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2014)
Abstract: The dynamics of the spread of ads that are more interesting and varied portrait of real freedom of communication that thrives in Indonesia after the change of government that strict monitoring of the messages being diffused to the public. Essentially it encourages free expression of creative ideas in the competition to market their goods and services. Critical observations on the development of advertising, shows that advertising still remains within the scope of science communication plays an important role in providing organizing messages limit. Nevertheless the practical aspects in society as a consumer or target advertising messages, advertising is not impossible also more focused on profit efforts. Of course the size of the business, good advertising is a creed which is able to attract consumer interest, although not impossible is not in line with the ideal advertisement should provide transparent and comprehensive information to the public.Abstrak: Dinamika penyebaran iklan yang semakin menarik dan variatif merupakan potret nyata kebebasan berkomunikasi yang tumbuh subur di Indonesia pasca pergantian pemerintahan yang melakukan pengawasan ketat terhadap pesan-pesan yang didifusikan kepada masyarakat. Hakikatnya kebebasan berekspresi memang mendorong munculnya ide kreatif dalam persaingan untuk memasarkan barang dan jasa. Pengamatan kritis terhadap berkembangnya periklanan, menunjukkan bahwa iklan masih tetap dalam lingkup ilmu komunikasi yang berperan penting dalam memberikan batasan pengorganisasian pesan. Kendati demikian dalam aspek yang praktis di masyarakat ataupun konsumen sebagai sasaran pesan iklan, bukan mustahil iklan juga lebih berfokus kepada upaya keuntungan. Tentu saja dalam ukuran bisnis, kredo iklan yang baik adalah yang mampu menarik minat konsumen, meskipun bukan mustahil tidak sejalan dengan iklan ideal yang seharusnya transparan dan komprehensif memberikan informasi kepada khalayak.